Study on Laccase, Peroxidase, Cellulase and Polyphenol Oxidase Enzyme Activities in Jatropha curcas L. - Kumar, R.V.; Tripathi, Yogendra K.; Yadav, V.P.; Ahlawat, S.P. (Indian Journal of Agroforestry, 2020)
Fifty accessions of Jatropha curcas were analyzed for their ability to produce laccase, cellulase, peroxidase and poly phenol oxidase enzymes through spectrophotometer in 90 days old seedlings. In general all accessions showed strong activities of laccase, and low production of peroxidase, polyp he no I oxidase and cellulase. Among all accessions, NRCJ- 32 produced highest activities of laccase, peroxidase, cellulase and poly phenol oxidase and accession NRCJ-75 showed lowest production of laccase, cellulase and polyphenol oxidase. Lowest production of peroxidase was observed in NRCJ-46. The results clearly demonstrate that these enzymes are expressed differentially during the growth and development of Jatropha curcas. Laccase and peroxidase enzymes are responsible for lignin degradation, which ultimately effects the growth and development of the plant. Simultaneously, cellulase and polyphenol oxidase effects the fruiting behaviour of the plant. Thus, the information generated will differentiate the accessions based on high enzymes activity leading to better growth and development.